Detection of Low-Signal Pulvinar Areas Using Diffusion-Weighted Imaging in Patients with Dementia Experiencing Visual Hallucinations - Mayuko Sugiura; Masayuki Satoh; Ken-ichi Tabei; Tomoki Saito; Mutsuki Mori; Makiko Abe; Hirotaka Kida; Masayuki Maeda; Hajime Sakuma; Hidekazu Tomimoto (Dementia and Geriatric Cognitive Disorders Extra, 2016)
Background: Little research has been conducted regarding the role of pulvinar nuclei in the pathogenesis of visual hallucinations due to the difficulty of assessing abnormalities in this region using conventional magnetic resonance imaging (MRI). The present study aimed to retrospectively investigate the relative abilities of diffusion-weighted imaging (DWI), fluid-attenuated inversion recovery (FLAIR), and susceptibility-weighted imaging (SWI) to visualize the pulvinar and to ascertain the relationship between pulvinar visualization and visual hallucinations. Methods: A retrospective analysis of 3T MRIs from 73 patients (31 males, 42 females; mean age 73.5 ± 12.7 years) of the Memory Clinic of Mie University Hospital was conducted. Correlations between pulvinar visualization and the following were analyzed: age, sex, education, hypertension, hyperlipidemia, diabetes mellitus, Mini-Mental State Examination score, Evans index, and visual hallucinations. Results: DWI detected low-signal pulvinar areas in approximately half of the patients (52.1%). Participants with pulvinar visualization were significantly older, and the pulvinar was more frequently visualized in patients who had experienced visual hallucinations compared to those who had not. No significant association was observed between whole brain atrophy and pulvinar visualization. Conclusions: The results of the present study indicate that diffusion-weighted 3T MRI is the most suitable method for the detection of pulvinar nuclei in patients with dementia experiencing visual hallucinations.